2015
DOI: 10.1093/nar/gkv068
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of a cell cycle associated HDAC1/2 complex reveals the structural basis for complex assembly and nucleosome targeting

Abstract: Recent proteomic studies have identified a novel histone deacetylase complex that is upregulated during mitosis and is associated with cyclin A. This complex is conserved from nematodes to man and contains histone deacetylases 1 and 2, the MIDEAS corepressor protein and a protein called DNTTIP1 whose function was hitherto poorly understood. Here, we report the structures of two domains from DNTTIP1. The amino-terminal region forms a tight dimerization domain with a novel structural fold that interacts with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 45 publications
3
67
1
Order By: Relevance
“…A sequence-specific DNA binding role appears to be unlikely, as the SWI/SNF complex is thought to be directed to specific sites within the genome by interacting with transcription factors. It is more probable that, as has been proposed for the homologous domain from DNTTIP1 ( Itoh et al., 2015 ), it acts as a chromatin binding module, perhaps only binding with high affinity to DNA within a particular chromatin environment. Crosslinking studies of yeast SWI/SNF nucleosome complexes have shown that the INI1 homolog SNF5, which does not contain the winged helix domain, associates with the histone octamer and not with nucleosomal DNA ( Dechassa et al., 2008 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A sequence-specific DNA binding role appears to be unlikely, as the SWI/SNF complex is thought to be directed to specific sites within the genome by interacting with transcription factors. It is more probable that, as has been proposed for the homologous domain from DNTTIP1 ( Itoh et al., 2015 ), it acts as a chromatin binding module, perhaps only binding with high affinity to DNA within a particular chromatin environment. Crosslinking studies of yeast SWI/SNF nucleosome complexes have shown that the INI1 homolog SNF5, which does not contain the winged helix domain, associates with the histone octamer and not with nucleosomal DNA ( Dechassa et al., 2008 ).…”
Section: Discussionmentioning
confidence: 95%
“…Comparing the structure with known structures using the program DALI ( Holm and Rosenstrom, 2010 ) revealed significant similarities to the dachshund homology domain (DHD) of SnoN ( Z score of 6.2). The SnoN domain is a member of a family of structurally related domains found exclusively in metazoan chromatin-associated proteins that includes the DHD domains of DACH1 and the SKI proto-oncogene ( Kim et al., 2002; Nyman et al., 2010; Wilson et al., 2004 ) as well as domains in the BCL6 co-repressor BCOR ( Junco et al., 2013 ) and DNTTIP1, a subunit of the HDAC1:MIDEAS co-repressor complex ( Itoh et al., 2015 ). The INI1 N-terminal domain also shows significant structural similarity to the winged helix DNA binding domain of the Mbp1 family of yeast cell cycle regulatory proteins ( Taylor et al., 1997; Xu et al., 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…MiDAC constitutes a stoichiometric tetrameric complex that requires the N-terminal dimerization domain of DNTTIP1 for assembly. The C terminus of DNTTIP1 mediates MiDAC recruitment to nucleosomes in vitro (Itoh, Fairall et al, 2015). MiDAC specifically associates with cyclin A2 (CCNA2) and cell cycle dependent kinase 2 and interacts more prominently with certain HDAC inhibitors in mitotically arrested versus non-synchronized proliferating cells, suggesting a role in cell cycle regulation (Bantscheff et al, 2011, Hein, Hubner et al, 2015, Huttlin, Ting et al, 2015, Pagliuca, Collins et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleosome remodelling and deacetylase (NuRD) complex is one of at least five corepressor complexes that recruits and activates class I histone deacetylase (HDACs) enzymes and directs their activity to chromatin ( Bantscheff et al, 2011 ; Guenther et al, 2000 ; Humphrey et al, 2001 ; Itoh et al, 2015 ; Kelly and Cowley, 2013 ; Laherty et al, 1997 ; Oberoi et al, 2011 ; Vermaak et al, 1999 ; Watson et al, 2012 ; Wen et al, 2000 ; Xue et al, 1998 ; Zhang et al, 1999 ). The NuRD complex plays a major role in the regulation of gene expression as well as being involved in chromatin organization, DNA damage repair, and genomic stability ( Denslow and Wade, 2007 ; Lai and Wade, 2011 ).…”
Section: Introductionmentioning
confidence: 99%